Praktik Manajemen Laba melalui Profitabilitas dan Leverage pada Perusahaan Manufaktur di Bursa Efek Indonesia - Edisah Putra Nainggolan; Ikhsan Abdullah (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
This study aims to determine the practice of earnings management is influenced by the profitability and leverage of food and beverage manufacturing companies listed on the Indonesia Stock Exchange. The profitability ratio in this study is measured by return on assets (ROA) and leverage is measured by debt to equity ratio (DER), while earnings management is measured by discretionary accruals (DA). This research approach uses quantitative associative which aims to determine the causal effect